Student teachers' cognition about L2 pronunciation instruction: A case study - Michael Burri (The Australian journal of teacher education, 2015)
In view of the minimal attention pronunciation teacher preparation has received in second language (L2) teacher education, this study examined the cognition (i.e. beliefs, thoughts, attitudes and knowledge) development of 15 student teachers during a postgraduate subject on pronunciation pedagogy offered at an Australian tertiary institution. Findings revealed that, as a result of taking the subject, student teachers' cognition shifted from teaching individual sounds (i.e. segmentals) to favouring a more balanced approach to pronunciation instruction. That is, teaching the melody of the English language (i.e. suprasegmentals) was seen as important as teaching segmentals. Non-native speakers' self-perceived pronunciation improvement, an increase in their awareness of their spoken English, and native/non-native collaboration played critical roles in facilitating participants' cognition growth. The findings also showed that cognition development is a complex process. The paper concludes with recommendations for preparing L2 teachers to teach English pronunciation in their classroom contexts.